Automatization of plasma density profile analysis by the multichannel microwave interferometer measurements for the Torsatron U-2M - Ocheretenko, V.L.; Berezhnyj, V.L.; Prokopenko, A.V.; Pinos, I.B. (Вопросы атомной науки и техники, 2008)
The paper presents the description of the density profile computing methods by the five-channel probing on the base of the developed program code and gives the results of model investigations.